A methodology for investigating the impact of medical countermeasures on the risk of exposure induced death. (May 2020) - Werneth, C.M.; Slaba, T.C.; Blattnig, S.R.; Huff, J.L.; Norman, R.B.
Abstract: The space radiation environment is composed of ionizing particles that may pose health risks to crew members during Low Earth Orbit (LEO) and deep space missions. NASA has established astronaut career radiation limits for cancer of 3% Risk of Exposure Induced Death (REID) at the 95% confidence level. The REID is the increased lifetime risk of death from cancer due to radiation exposure in comparison to an unexposed background population and has been traditionally mitigated by passive shielding design concepts and limiting safe days in space. Additional reduction in radiation exposure risk may be achieved with Medical Countermeasures (MCM). Recent meta-analyses have demonstrated the efficacy of aspirin in the reduction of the background colorectal cancer incidence and mortality rates for specific cohorts. Additional studies of warfarin in patients greater than 50 years of age have indicated statistically significant decreases in stomach, bladder, brain, prostate, and lung cancer incidence as compared to control groups. While ultimate selection of suitable countermeasures will be the responsibility of flight surgeons, this paper presents a general methodology for incorporating MCM into the NASA Space Radiation Cancer Risk model and includes modifications of the background mortality rates (hazard rates) and the radiation risk coefficients to numerically quantify the benefits of MCM. As examples of the method, aspirin and warfarin will be employed as MCM in a sensitivity analysis to compute the REID for astronauts embarking on a one-year deep space mission scenario.